Redescription of the Type Species of the Genus Argistes (Aranei, Liocranidae) - Yu. M. Marusik (National Academy of Sciences of Ukraine, 2022)
A previously unknown female of Argistes velox Simon, 1897, type species of the genus Argistes, is described and the male is redescribed. Th e species is known only from Sri Lanka. Status of the genus is briefly commented.